The Invention of a New Religion - Chamberlain, Basil Hall, 1850-1935 (Salt Lake City, UT : Project Gutenberg, 2001)
"The Invention of a New Religion" by Basil Hall Chamberlain is a critical essay written in the early 20th century. The book examines the emergence of a new form of religion in Japan, specifically focusing on the worship of the Emperor as a divine figure alongside the promotion of patriotic ideologies. Chamberlain, an esteemed scholar of Japanese culture, analyzes how contemporary Japanese society has crafted this new religious framework, influenced by political needs and historical contexts. In this insightful work, Chamberlain argues that the new Japanese religion arose as a construct to unify the nation and serve the interests of the governing elite. He discusses how the Shinto principles were revitalized to support the Emperor's authority and legitimize the state's power, while drawing parallels with historical examples of fabricated religious identities. He critiques the manipulation of history and mythology by the Japanese bureaucracy, emphasizing the contradictions inherent in their narrative of loyalty and empowerment. Throughout the book, Chamberlain illustrates how this constructed belief system affects not only the political landscape but also the cultural identity of the Japanese people, creating a complex relationship between historical truth and contemporary belief. (This is an automatically generated summary.)
Release date is 2001-02-01
Produced by Peter Evans, and David Widger
Keywords: Japan -- Civilization; Japan -- Religion